2013
DOI: 10.5755/j01.em.18.2.4732
|View full text |Cite
|
Sign up to set email alerts
|

Lean Manufacturing Implementation and Progress Measurement

Abstract: Applying Lean manufacturing philosophy is one of the most important concepts that help enterprises to gain competitive advantage in the world market. Lean manufacturing or lean production is a production practice, which regards the use of resources for any work other than the creation of value for the end customer, as waste. Although a lot of companies started implementing Lean concept, and the number of Lean tools, techniques and technologies available to improve operational performance are growing rapidly, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…Thus, manufacturing firm have implemented various sustainable practices to reduce carbon footprint, remain competitive and as an answer to the global concern of environmental degradation. Some of the practices are known as Environmentally Conscious (Despeisse et al, 2012), Lean Manufacturing (Vienazindiene & Ciarniene, 2013) and Green Manufacturing (Rehman & Shrivastava, 2013). Scholars such as (Hart & Dowell, 2011), focus on large corporations, as is implicit in the labels corporate social and environmental responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, manufacturing firm have implemented various sustainable practices to reduce carbon footprint, remain competitive and as an answer to the global concern of environmental degradation. Some of the practices are known as Environmentally Conscious (Despeisse et al, 2012), Lean Manufacturing (Vienazindiene & Ciarniene, 2013) and Green Manufacturing (Rehman & Shrivastava, 2013). Scholars such as (Hart & Dowell, 2011), focus on large corporations, as is implicit in the labels corporate social and environmental responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…By being frequently heard on-site and participating in kaizen events, they felt as an active part of the solution and so they became more committed in their work. The involvement of the workers and the change in terms of mentality were essential to implement new ways of working but also to keep the continuous improvement process on track (Hines, Holwe, and Rich 2004;Mann 2010;Vienazindiene and Ciarniene 2013). The results achieved in the case study suggest that the remaining solutions from the action plan could lead the production process to the proposed state and should therefore be implemented.…”
Section: Discussionmentioning
confidence: 95%
“…Some authors have suggested ways to delineate the required steps for implementing lean (Black 2007;Serrano Lasa, Castro, and Laburu 2009;Vienazindiene and Ciarniene 2013) but there is still, according to Marodin and Saurin (2013), the need for further research so as to define coherent methods for implementing lean systems.…”
Section: Lean Manufacturing and Continuous Improvementmentioning
confidence: 99%
“…An effort for initiating a new order of things to implement lean is not easy task (Bhasin and Burcher, 2006). Barriers of LM may be specific to the type of organisation and economic sector they are operating (Vienazindiene and Ciarniene, 2013). Various obstructs to LM have been recognised by various researchers such as history of past failures, management of changes, increased intergroup conflict and complex behavioural related issues (Sarhan and Fox, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%